Socio-technical embeddedness of organic agriculture in nearby circuits (Polis (Santiago), 2020)
This article deals with the phenomenon of social embeddedness in three cases of circuits for commercialization of organic products, studied comparatively. Ecological Fair of Laranjeiras do Sul, Orgânicos Rio de Una and South Circuit of Ecovida Network. We propose to recover the social immersion on the organizations, related to the farmers, as the labor market for the thesis of Mark Granovetter. We visit the categories of embeddedness, reflecting the expressions from Polanyi, followed by the cases studied, by the method of interviews with semi-structured scripts, analyzed in clusters of meanings. Decision-making processes, communities and farmer participation are highlighted. We point out the overcoming of limitations in market-centered frameworks, through socio-technical development, when reestablishing access channels, knowledge dissemination, exchange among networks, in interactions by the force of social links and to the extent that it is preponderant for decisions on agro-ecological transaction
Keywords: Improvement; reciprocity; institutions; agroecology; incorporation.